Collaterals: An Important Determinant of Prolonged Ischemic Penumbra Versus Rapid Cerebral Infarction? - Marsh, Elisabeth Breese; Leigh, Richard; Radvany, Martin; Gailloud, Philippe; Llinas, Rafael H. (Frontiers in Neurology, 2014)
Intravenous tissue plasminogen activator is the mainstay for the treatment of acute ischemic stroke in patients presenting within 4.5 hours of symptom onset. Studies have demonstrated that treating patients early leads to improved long term outcomes. MR imaging currently allows quantification of the ischemic penumbra in order to better identify individuals most likely to benefit from intervention, irrespective of “time last seen normal.” Its increasing use in clinical practice has demonstrated individual differences in rate of infarction. One explanation for this variability is a difference in collateral blood flow. We report two cases that highlight the individual variability of infarction rate, and discuss potential underlying mechanisms that may influence treatment decisions and outcomes.